Euro adoption and inflation stability: Early evidence from Croatia and the Czech Republic - Soper, Carolyne C. (Journal of Finance and Financial Law, 2025)
The purpose of the article is to explore the link between monetary policy regimes and inflation dynamics in small open economies. Croatia and the Czech Republic provide a natural experiment for examining how small open economies with different monetary frameworks respond to global and regional shocks, including euro adoption and other external disturbances. The analysis sheds light on how institutional arrangements affect the stability of inflation rates in the presence of global shocks.Methodology includes a Vector Autoregression (VAR) approach with monthly data covering the period from 2000 to 2024 and is complemented by Granger causality tests, as well as a structural break analysis to account for major events such as the global financial crisis in 2008, the COVID-19 pandemic in 2020, the 2022 European energy shock, and Croatia’s euro adoption.The results of the empirical analysis reveal that euro adoption is associated with reduced short-term inflation volatility but weaker responsiveness to external shocks, while monetary independence allows greater policy flexibility at the cost of heightened inflation variability. These findings provide early evidence on the inflation-stabilizing role of euro adoption and contribute to ongoing policy debates on monetary integration within the European Union.